Domain-specific consideration of future consequences and early alcohol use: a bivariate and person-centered analysis. (4th March 2022) - McKay, Michael T.; Perry, John L.; Cole, Jon C.
Abstract: Research into temporal psychology, and in particular its relationship with health behaviors, has grown exponentially in recent years. Accordingly, studies have shown that how individuals think and feel about the past, present, and future, is significantly related to alcohol-use behaviors. This has been shown to be particularly true where studies have applied person-centered analyses rather than just bivariate analyses. The present study sought to examine the relationship between scores on one temporal psychology measure (The Domain-Specific Consideration of Future Consequences [CFC] scale) and alcohol use behaviors in a large sample of adolescents in the United Kingdom (N = 2, 199; 42.4% female). Scores on the CFC measure were operationalized both domain-specifically, and by means of cluster analyses. In bivariate analyses, reduced likelihood of past month consumption of a full drink and Heavy Episodic Drinking were significantly associated with CFC-scores, but did not appear to be domain-specific. In unadjusted analyses, CFC cluster membership was significantly related to alcohol use variables. However, when adjusted for sex, location, and sensation seeking, the result for Heavy Episodic Drinking became non-significant. Results are discussed in the context of current temporal psychology.